Prevalence of potentially inappropriate medication and its correlates in elderly hospitalized patients: A cross-sectional study based on Beers criteria - Rishabh Sharma; Parveen Bansal; Ravinder Garg; Ravi Ranjan; Rakesh Kumar; Malika Arora (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: The increase in the prescription of potentially inappropriate medication (PIM) in older adults with significant health consequences is a global concern. This study aimed to determine the prevalence of PIM prescription in older adults as identified by Beers criteria 2015 and 2019. MATERIALS AND METHODS: A cross-sectional study was carried out in older adults aged >65 years at a tertiary care postgraduate teaching hospital. All patients aged ≥65 years irrespective of their gender, admitted in the medical ward of the hospital with single/multiple comorbidities, and prescribed at least one daily medication, were included in the study. Data of patient history, patient case sheet, medication charts, laboratory reports, as well as radiological examinations test reports were retrieved from their files and were captured in a prevalidated data collection form. SPSS used for data analysis; multivariate logistic regression was used to determine the predictors of PIM prescribing and odds ratios (ORs) and 95% confidence intervals for ORs were computed. RESULTS: Study included 323 patients; 61.3% were male, 74% patients were 65-70 years of age, and 78% patients were illiterate. The overall prevalence of PIM uses according to the Beers criteria 2015 and 2019 was 60.1% and 61.9%, respectively. No association found between PIMs prescribes and diagnosis category. Male gender, age 76-80 years, and education 10-12th class were found to be significantly related to PIM prescription. CONCLUSION: This study reflects a critical view of noncompliance of Beers criteria for geriatric healthcare even in tertiary care hospitals in India. Creatinine clearance rate should be kept in view when prescribing medicines for elderly inpatients.